Quality model in use for bank web portals in Peru - Sobero, Fany (2020)
Electronic banking emerged as a result of the increase in customer demand as an easily accessible alternative channel, which saves time on their physical travel, and it is important that the customer feel confident and that this channel meets their needs. Banking applications can generate latent risks if they have not been properly implemented, thus generating a bad perception of bank services in general. For this reason, in the literature there are various studies on the application of quality models in various areas, but they have not been applied to Peruvian electronic banking, for this reason, in this paper, we propose a quality model in use for portable web banking. In Peru that allows to know the perception when using the electronic channel. The model consists of 6 characteristics and 11 sub characteristics, which were obtained by the assessment of experts in electronic banking. To corroborate the validity of the data, Crombach’s alpha was applied, obtaining 85% reliability of the data. As a main result, it was obtained that the sub-characteristic “security” is shown as the most important, this factor being the most sensitive as a determinant of the adoption of electronic channels, followed by “efficiency” and “effectiveness”.